2012
DOI: 10.1155/2012/606424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12-WeekBacopa monnieriConsumption on Attention, Cognitive Processing, Working Memory, and Functions of Both Cholinergic and Monoaminergic Systems in Healthy Elderly Volunteers

Abstract: At present, the scientific evidence concerning the effect of Bacopa monnieri on brain activity together with working memory is less available. Therefore, we aimed to determine the effect of B. monnieri on attention, cognitive processing, working memory, and cholinergic and monoaminergic functions in healthy elderly. A randomized double-blind placebo-controlled design was utilized. Sixty healthy elderly subjects (mean age 62.62 years; SD 6.46), consisting of 23 males and 37 females, received either a standardiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 32 publications
(29 reference statements)
6
46
0
Order By: Relevance
“…A dose-dependent free radical scavenging capacity and a protective effect against DNA damage by methanolic extract of B. monnieri was also reported by Russo et al [26] and Anand et al [20]. Lipid peroxidation brought about by FeSO 4 and cumene hydroperoxide was significantly reduced by bacopa treatment in animal models by chelating Fe 2+ [27]. Radical quenching activity of ethanol and aqueous extracts of B. monnieri was also widely reported [28].…”
Section: Basics Of Bacopa Monnierimentioning
confidence: 63%
“…A dose-dependent free radical scavenging capacity and a protective effect against DNA damage by methanolic extract of B. monnieri was also reported by Russo et al [26] and Anand et al [20]. Lipid peroxidation brought about by FeSO 4 and cumene hydroperoxide was significantly reduced by bacopa treatment in animal models by chelating Fe 2+ [27]. Radical quenching activity of ethanol and aqueous extracts of B. monnieri was also widely reported [28].…”
Section: Basics Of Bacopa Monnierimentioning
confidence: 63%
“…One of the included studies also demonstrated a decreased latency of evoked potentials to stimuli (i.e. faster cerebro-electrical processing) using EEG [ 219 ].…”
Section: Terpenesmentioning
confidence: 99%
“…The bacosides also aid in repair of damaged neurons by enhancing kinase activity, neuronal synthesis, restoration of synaptic activity, and nerve impulse transmission (Singh and Dhawan, 1997). Peth-Nui et al (2012) demonstrated that B. monnieri suppresses acetylcholinesterase activity resulting in enhanced Peng et al, 2010;Ghosh et al, 2011a;Patil et al, 2014Antidepressant activity Shen et al, 2009Hazra et al, 2012;Sindhu et al, 2014;Ramana Murty Kadali et al, 2014;Mannan et al, 2015Antidiabetic activity Ghosh et al, 2008Ghosh et al, 2011b;Prasenjit et al, Uabundit et al, 2010;Aguiar and Borowski, 2013 cholinergic function, which in turn enhances attention and memory processing and increases working memory in elderly people.…”
Section: Phytochemical Substancesmentioning
confidence: 99%